Extended Reality in Spatial Sciences: A Review of Research Challenges and Future Directions - Çöltekin, Arzu; Lochhead, Ian; Madden, Marguerite; Christophe, Sidonie; Devaux, Alexandre; Pettit, Christopher; Lock, Oliver; Shukla, Shashwat; Herman, Lukáš; Stachoň, Zdeněk; Kubíček, Petr; Snopková, Dajana; et al. (ISPRS international journal of geo-information, 2020)
This manuscript identifies and documents unsolved problems and research challenges in the extended reality (XR) domain (i.e., virtual (VR), augmented (AR), and mixed reality (MR)). The manuscript is structured to include technology, design, and human factor perspectives. The text is visualization/display-focused, that is, other modalities such as audio, haptic, smell, and touch, while important for XR, are beyond the scope of this paper. We further narrow our focus to mainly geospatial research, with necessary deviations to other domains where these technologies are widely researched. The main objective of the study is to provide an overview of broader research challenges and directions in XR, especially in spatial sciences. Aside from the research challenges identified based on a comprehensive literature review, we provide case studies with original results from our own studies in each section as examples to demonstrate the relevance of the challenges in the current research. We believe that this paper will be of relevance to anyone who has scientific interest in extended reality, and/or uses these systems in their research.